The Fear of COVID-19 Scale of Student's University - Naji, Faten Abd Aljabbar (Al-Adab Journal, 2021)
The aim of the research is to know the fear of the Covid-19 epidemic among university students, and the researcher used the (Descriptive Research Methodology). College, including (14) scientific colleges and (10) humanitarian colleges. The sample of the research consisted of (200) male and female students from the research community distributed among (four) colleges chosen randomly from the University of Baghdad, two scientific colleges and two human faculties, and a gender variable representation (males - females), equal, by (100) males and (100) From females, the researcher used the fear scale of the Covid-19 epidemic for (Ahorsu et al, 2020). The validity (translation, apparent translation,) and consistency were verified using and to extract the results of the research, the researcher used the T-test for a sample One and the T-test for two independent samples. Research results: - The research showed the existence of statistically significant differences among student's university in fear of the Covid-19 epidemic in general. There is difference in fear of the Covid-19 epidemic, according to the gender variable.